Analisis Faktor-faktor yang mempengaruhi Keberhasilan Implementasi Sistem Informasi Manajemen (SIM) Perspektif Studi Kasus - Mintawati, Hesri; Simangunsong, Bonse Aris Mandala Putra; Suhardi, Mulyadi; Puspita, Dela; Safhira, Futri; Indah, Neng Susan Wulan Purnama (Neolectura, 2023)
The implementation of Management Information Systems (MIS) is essential for organizations to enhance operational efficiency and competitiveness. However, the success of MIS implementation is influenced by various complex factors. This study aims to analyze the factors affecting the success of MIS implementation from the perspective of a case study in a medium- sized manufacturing company. Through interviews, observations, and document analysis, seven key factors were identified: top management support, user involvement, training and mentoring, alignment with business processes, information technology infrastructure, organizational culture, and change management. These findings provide valuable insights for organizations to effectively manage MIS implementation and achieve expected benefits. The theoretical and practical implications of this research are also discussed.